Hubungan Dukungan Sosial Keluarga Dengan Frekuensi Kekambuhan Pasien Epilepsi Di Ruang Rawat Jalan Rumah Sakit Jiwa Provinsi Jawa Barat Tahun 2022 - Fitri Komalasari; Asep Solihat (Pusat Riset dan Inovasi Nasional, 2022)
: Family support is one of the factors that may affect relapse in patients with epilepsy. Epilepsy is one a illness of brains and nerve’s with the highest incidence to four from ten diagnose in the Mental Hospital of West Java Province in January-march 2022, with the incidence rate of as much as 500 patients. This study aims to determine the relationship of social support of families with epilepsy patients relapse frequency in the out patient Mental Hospital of West Java Province. Design of quantitative research with cross sectional approach and the sample amounted to 62 patients with epilepsy. Results of that study (40,3%) less family support, (9,7%) were family social support, and (50%) good family support. Results for the frequency of relapse in patients with epilepsy (38,7%) high recurrence rate (32,3%) recurrence rate was, and (29%) recurrence rate is low. The results using spearman rank test was obtained ρ value of 0,000 < 0,05. Means Ho is rejected, this shows there is a relationship of social support for families with epilepsy patients relapse frequency in the out patient Mental Hospital of West Java Province. Spearman correlation coefficients obtained a value of 0,603 which means that there is a significant relationship between social support of families with the frequency of relapse in patients with epilepsy. So it is suggested that the education in the family in order to continue to provide support to patients with epilepsy and is expected to nurse a mental hospital to provide information to families about the importance of the meaning of family social support for patients with epilepsy.